2021
DOI: 10.7554/elife.66638
|View full text |Cite
|
Sign up to set email alerts
|

Intact synapse structure and function after combined knockout of PTPδ, PTPσ, and LAR

Abstract: It has long been proposed that Leukocyte common Antigen-Related Receptor Protein Tyrosine Phosphatases (LAR-RPTPs) are cell-adhesion proteins that control synapse assembly. Their synaptic nanoscale localization, however, is not established, and synapse fine structure after knockout of the three vertebrate LAR-RPTPs (PTPδ, PTPσ and LAR) has not been tested. Here, superresolution microscopy reveals that PTPδ localizes to the synaptic cleft precisely apposed to postsynaptic scaffolds of excitatory and inhibitory … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Moreover, LAR-PTPRs appear to interact with neurexins in cis, possibly via the heparan-sulfate modification of neurexins ( Han et al, 2020 ). Deletion of all three LAR-PTPRs causes no decrease in synapse numbers, demonstrating that they alone are not essential for making a synapse, but induce an ∼40% decrease in NMDAR-mediated synaptic responses without significantly altering AMPAR-mediated responses ( Sclip and Südhof, 2020 ; Emperador-Melero et al, 2021 ). Although this phenotype resembles the effect of neurexin-1 SS4-alternative splicing on NMDAR-mediated synaptic responses, in the case of neurexin-1, the surface levels of NMDARs are changed ( Dai et al, 2019 ), whereas in the case of the LAR-PTPR deletion, the surface levels of NMDARs were not impaired ( Sclip and Südhof, 2020 ).…”
Section: Shaping Synapse Propertiesmentioning
confidence: 99%
“…Moreover, LAR-PTPRs appear to interact with neurexins in cis, possibly via the heparan-sulfate modification of neurexins ( Han et al, 2020 ). Deletion of all three LAR-PTPRs causes no decrease in synapse numbers, demonstrating that they alone are not essential for making a synapse, but induce an ∼40% decrease in NMDAR-mediated synaptic responses without significantly altering AMPAR-mediated responses ( Sclip and Südhof, 2020 ; Emperador-Melero et al, 2021 ). Although this phenotype resembles the effect of neurexin-1 SS4-alternative splicing on NMDAR-mediated synaptic responses, in the case of neurexin-1, the surface levels of NMDARs are changed ( Dai et al, 2019 ), whereas in the case of the LAR-PTPR deletion, the surface levels of NMDARs were not impaired ( Sclip and Südhof, 2020 ).…”
Section: Shaping Synapse Propertiesmentioning
confidence: 99%
“…Indeed, both LARs and Neurexins are strongly synaptogenic 119 , 120 . Surprisingly, however, neither LARs nor Neurexins appear to be generally required for synapse formation, supporting the notion of molecular redundancies 121 , 122 . Not even loss of three neurexins or all three LARs in mice appears to reduce synapse numbers, whereas only a conditional sixtuple-knockout of these LARs and Neurexins leads to an at least 50% reduction of synapse numbers between Purkinje cells and deep cerebellar nuclei 118 .…”
Section: Main Textmentioning
confidence: 76%
“…Mice lacking RPTσ , on the contrary, showed increased synapse density ( Horn et al, 2012 ). Studies on triple knockout mice either in vivo using virus carrying Cre recombinase or in cultured neurons showed that PTPδ , PTPσ , and LAR triple knockout do not affect the development and function of synapses ( Sclip and Sudhof, 2020 ; Emperador-Melero et al, 2021 ).…”
Section: Cell Adhesion Molecules Bridging the Pre- And Post-synaptic ...mentioning
confidence: 99%